2017
DOI: 10.1007/s00280-017-3356-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non-coding RNA KCNQ1OT1 depressed chemoresistance to paclitaxel in lung adenocarcinoma

Abstract: Lung cancer, with the highest morbidity and second highest death rates, is one of the most common cancers in both males and females worldwide. Lung adenocarcinoma (LAD) is the main lung cancer class. KCNQ1 Opposite Strand/Antisense Transcript 1 (KCNQ1OT1) gene is an lncRNA which had been reported high-expression in colorectal cancer. In this study, the expression of KCNQ1OT1 was confirmed to be highly expressed in LAD tissues and cells contrast to control tissues and cells, and high KCNQ1OT1 expression correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 23 publications
4
68
0
Order By: Relevance
“…KCNQ1OT1 also reached statistical significance in the validation set after multivariate analysis. Higher expression levels of KCNQ1OT1 have been shown in tissues from solid tumors including colorectal cancer, and lung adenocarcinoma compared to normal mucosa. Interestingly, high mRNA expression levels of KCNQ1OT1 were correlated with paclitaxel resistance in lung cancer patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…KCNQ1OT1 also reached statistical significance in the validation set after multivariate analysis. Higher expression levels of KCNQ1OT1 have been shown in tissues from solid tumors including colorectal cancer, and lung adenocarcinoma compared to normal mucosa. Interestingly, high mRNA expression levels of KCNQ1OT1 were correlated with paclitaxel resistance in lung cancer patients.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, high mRNA expression levels of KCNQ1OT1 were correlated with paclitaxel resistance in lung cancer patients. Also, in vitro silencing of KCNQ1OT1 in paclitaxel‐resistant A549/PA cells restored paclitaxel sensitivity . In CRC, an aberrant expression and function of KCNQ1OT1 have been reported .…”
Section: Discussionmentioning
confidence: 92%
“…The lncRNA Kcnq1ot1, the full name of which is KCNQ1 overlapping transcript 1, is located in the KCNQ1 locus at 11p15.5 [13]. Kcnq1ot1 has been reported to be associated with many disorders, particularly those related to heart disease [14][15][16][17]. Li et al [14] indicated that suppression of Kcnq1ot1 might prevent myocardial I/R injury following acute myocardial infarction via regulating AdipoR1.…”
Section: Introductionmentioning
confidence: 99%
“…At present, few studies regarding its aberrant expression and function in cancers have been reported. Ren et al revealed that KCNQ1OT1 played an oncogenic role in regulating malignant behavior and chemoresistance of lung adenocarcinoma cells [19]. Sunamura et al indicated that regulation of KCNQ1OT1 lncRNA by β-catenin signaling might be involved in multiple processes of colorectal cancer development [20].…”
Section: Introductionmentioning
confidence: 99%